1994
DOI: 10.1111/j.2044-8317.1994.tb01036.x
|View full text |Cite
|
Sign up to set email alerts
|

Bootstrapping latent variable models for binary response

Abstract: Estimated asymptotic variances for the estimates of the parameters in a logit-probit model for binary response data are unreliable for moderate sized samples. We show how bootstrapping gives a bctter idea of the sampling distribution of the estimators, and can also allow an assessment of the reliability of the scoring of individuals on the latent scale. lntroductionWhen a one-factor logit-probit model is fitted by maximum likelihood to binary (0, I ) response data, one very often wishes to score the observed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…It is well known that maximum likelihood estimation of latent (trait) models with binary or ordered categorical data present modeling challenges (Albanese & Knott, 1994; Sterba et al, 2010). This problem is further magnified in rare-event behavioral data, where many indicators demonstrate a preponderance of nonevents (i.e., the disrupted maternal behavior does not occur).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that maximum likelihood estimation of latent (trait) models with binary or ordered categorical data present modeling challenges (Albanese & Knott, 1994; Sterba et al, 2010). This problem is further magnified in rare-event behavioral data, where many indicators demonstrate a preponderance of nonevents (i.e., the disrupted maternal behavior does not occur).…”
Section: Methodsmentioning
confidence: 99%
“…Sparse data response patterns may lead to extreme parameter and/or standard error estimates, which are unstable (de Menezes, 1999) or frequently drift into inadmissible regions (Swaminathan, Hambleton, Sireci, Xing, & Rizavi, 2003). Albanese and Knott (1994) showed that estimated asymptotic variances of the parameter estimates in a one-factor model for binary data are unreliable. They arrived at a better idea of the sampling distribution of the parameter estimates by bootstrapping.…”
Section: Methodsmentioning
confidence: 99%
“…However, when we consider the literature on latent class models, only a small number of references have addressed the topic (for example, Bartholomew (1987), while focusing on latent variable models, and Tanner (1993), when referring to estimates from E-M algorithm s). Albanese & Knott (1994), focusing upon latent trait models, and speci cally the one-factor logit model for binary data, have shown that the estimated asymptotic variances of the parameter estimates are unreliable. They arrived at a better idea of the sampling distribution of the parameter estimates by bootstrappin g. In their study, they generated 100 pseudoreplicates from the original data, by sampling individuals with replacement, and from the model, by using the maximum likelihood estimates of the parameters.…”
Section: The Asymptotic Standard Errors Of the Parameter Estimatesmentioning
confidence: 99%
“…On the contrary, when one refers to the literature, the lack of reliability of asymptotic estimates in the presence of extreme parameter values has been reported. For example, in the context of the one-factor logit-probit model, the asymptotic estimates were found to be unreliable (Albanese & Knott, 1994); in an investigation of possible adjustments to the log-likelihoo d ratio statistic, problem s in coping with very small parameters were experienced (Holt & MacReady, 1989).…”
Section: Problems In Computing Asymptotic Standard Errorsmentioning
confidence: 99%
“…Foram obtidas também as idades do aparecimento/desaparecimento de comportamentos considerados relevantes. As dificuldades para efetuar as análises quantitativas, devido ao grande volume de dados gerados nos estudos de Panico (1984Panico ( ,1987 (Agresti 1990, Bishop et al 1980, Conover 1980, Cox 1970, Mead 1989, Siegel 1975 de Diament (1976) (Albanese 1990, Anderson 1976, Bartholomew 1984, Bock 1975, Everitt 1978, Johnson e Wichem 1984, Knott & Albanese 1992, Morrison 1976…”
Section: Introductionunclassified